USING SCRIBING TECHNOLOGY IN COMPUTER SCIENCE LESSONS - S.V. Mamadzhanova (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the essence of students' visual thinking as a psychological and pedagogical phenomenon. Attention is directed to the methodological features of using scribing in computer science lessons in order to activate logical thinking, structure educational information and quickly memorize it by students. The main function of the method of presenting information using scribing is the ability to quickly, efficiently and visually convey information to students.